Systematic Evaluation of Fluorination as Modification for Peptide‐Based Fusion Inhibitors against HIV‐1 Infection. (22nd October 2021) - Huhmann, Susanne; Nyakatura, Elisabeth K.; Rohrhofer, Anette; Moschner, Johann; Schmidt, Barbara; Eichler, Jutta; Roth, Christian; Koksch, Beate
Abstract: With the emergence of novel viruses, the development of new antivirals is more urgent than ever. A key step in human immunodeficiency virus type 1 (HIV‐1) infection is six‐helix bundle formation within the envelope protein subunit gp41. Selective disruption of bundle formation by peptides has been shown to be effective; however, these drugs, exemplified by T20, are prone to rapid clearance from the patient. The incorporation of non‐natural amino acids is known to improve these pharmacokinetic properties. Here, we evaluate a peptide inhibitor in which a critical Ile residue is replaced by fluorinated analogues. We characterized the influence of the fluorinated analogues on the biophysical properties of the peptide. Furthermore, we show that the fluorinated peptides can block HIV‐1 infection of target cells at nanomolar levels. These findings demonstrate that fluorinated amino acids are appropriate tools for the development of novel peptide therapeutics. Abstract : Fluorinated variants of an HIV entry inhibitor inspired by clinically applied T20 were systematically studied. The results reveal six‐helix bundle formation for the fluorine‐containing sequences in the presence of wildtype N ‐terminal heptad repeat peptide of gp41. X‐ray crystal structures confirm favorable packing of the fluorinated groups and in vitro infection experiments with CEMx174 SEAP cells reveal nanomolar inhibition.